The Fine root dynamics after stand-replacing fire and clearcutting in the boreal forest of central Canada - Yuan, Zhiyou (2011)
In boreal forest ecosystems, stand age is a key driver of forest ecosystem productivity, carbon storage/sequestration, and other ecosystem functions. The age-related decline of aboveground productivity is well known in secondary forests after stand-replacing disturbances, however, how belowground root system changes with stand age is not well understood. Both fire and harvesting (mostly mechanical clearcutting) are also well known to be two main disturbances in boreal forests. These two disturbances are two distinct processes in terms of ecological effects, one is a natural disturbance, and the other is an anthropogenic one, resulting in different regeneration substrates, coarse woody debris structures, and understory vegetation communities. However, direct comparisons of belowground root dynamics between these two disturbance types within the same region are not common. In this present study, a boreal forest chronosequence in northern Ontario that spans over 200 years (3-, 1 0-, 29-, 94-, 142- and 205-year old for postfire stands and 3-, 1 0-, and 29-year old for post-clearcutting stands) was used to study how ecosystem functions such as the dynamics of fine roots (::S2 mm in diameter) vary with stand ages and disturbances.